Major Congenital Malformations of Gastrointestinal Tract Among Neonates Presenting to Tertiary Care - Saba Sohrab, Talha Shabbir, Rubina Kousar, Sadam Hussain, Quratulain Siddique, Saleem Ahmed Khoso, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Major congenital malformations of gastrointestinal tract (CMGIT), are usually manifested in early neonatal period by signs of intestinal obstruction and may be life threatening. A broad spectrum of Gastrointestinal Tract (GIT) anomalies can be seen including both upper and lower GIT. As compared to other congenital anomalies, GIT anomalies are not well studied and till now very few studies have reported prevalence and pattern of GIT malformations. Objective: To determine different type of common gastrointestinal anomalies among neonates presenting at tertiary care hospital. Methods: This descriptive cross sectional study was done at National Institute of Child Health (NICH) Karachi over period of 6 months, from 1-8-17 to 31-1-18. All neonates presenting to emergency department and got hospitalized with CMGIT were enrolled. Results: There were 35 neonates enrolled with CMGIT. Out of these 16(45.7%) were male and 19(54.3%) were females. Mean age 9.4+3.82 (range 1-20) days. Mean weight was 2.5±0.98 (range 0.5-4.5) kg. Mean duration of symptoms was 5.8+1.72 (range 1-9) days. Among the CMGIT, 12 (34.3%) cases were of Anorectal malformation, persistent Vitelline duct was found in 6 (17.1%), Intestinal atresia in 4(11.4%), Intestinal stenosis in 5(14.3%), Hirshsprung disease in 4(11.4%) and Exomphalos in 4 (11.4%). Conclusion: Anorectal malformations were most common anomaly followed by persistent vitelline duct. Antenatal follow up and anomaly scan of all neonates should be done. Keywords: Gastrointestinal anomaly, Neonates, congenital anomaly.